Analisis Hukum Islam Mengenai Perbedaan Hak Waris antara Anak Kandung dan Anak Angkat dalam Hukum Adat Batak Toba - Grace Claudia Valerina Saragih; Kevin Cornelius Manurung; Mhiranda Theresia Sitorus; Syuratty Astuti Rahayu Manalu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The distribution of inheritance is an important issue in Indonesian society which adheres to a plural legal system, namely Islamic law, customary law, and western civil law. One of the issues that often raises differences of opinion is the position of biological children and adopted children as heirs. In Islamic law, the right to inherit is based on the relationship of the nasab so that the biological child gets a clear share, while the adopted child does not have the right to inherit but can still be given a share through a grant or obligatory will. In contrast, Toba Batak customary law emphasizes the patrilineal principle, whereby sons, including legitimate adopted children through mangain customary ceremonies, are positioned as the successors of the clan and are entitled to inheritance except hereditary inheritance. This study uses a literature study method by examining literature related to Islamic law and Batak Toba customary law and qualitatively analyzed. The results of the study show that the difference in principles between these two legal systems gives birth to social and legal conflicts in the Batak Muslim society, especially when religious and customary values must be carried out together. However, opportunities for harmonization remain open through the application of the principle of justice that recognizes the position of adopted children in customary structures, as well as upholding sharia by granting rights through the mechanism of compulsory wills. These findings emphasize the need for an integrative approach in resolving inheritance disputes in order to create legal certainty, social justice, and maintain cultural and religious harmony.